2016
DOI: 10.22401/jnus.19.2.06
|View full text |Cite
|
Sign up to set email alerts
|

Study the Effect of Anastrozole on Estradiol and Cytochrome P450 (Aromatase Enzyme) in Postmenopausal Breast Cancer Patients

Abstract: In this study sixty patients were selected according to a positive estrogen receptor. All of 60 naturally or surgically postmenopausal women that had a diagnosis of breast cancer verified by histology breast cancer. Subdivided to with hormone treatment or without any treatment, Forty patients (group P1) with the ages range from 46 to 75 years, and were being treated with an aromatase inhibitor, Arimidex (1 mg) once daily, and another twenty (group P2) as newly diagnosed of breast cancer with ages ranging from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Recently, we reported the effect of anastrozole levels on estradiol in women with postmenopausal breast cancer. Strong positive correlations were found between serum aromatase and estradiol (r = 0.79-0.82) 18. We have also investigated the effect of aryl phosphonate derivatives on human breast cancer cells (MCF7) and liver carcinoma cell line (HepG2) 19.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported the effect of anastrozole levels on estradiol in women with postmenopausal breast cancer. Strong positive correlations were found between serum aromatase and estradiol (r = 0.79-0.82) 18. We have also investigated the effect of aryl phosphonate derivatives on human breast cancer cells (MCF7) and liver carcinoma cell line (HepG2) 19.…”
mentioning
confidence: 99%
“…Strong positive correlations were found between serum aromatase and estradiol (r = 0.79-0.82). 18 We have also investigated the effect of aryl phosphonate derivatives on human breast cancer cells (MCF7) and liver carcinoma cell line (HepG2). 19 The MCF7 cancer cell line is a very sensitive to estrogen receptor and can be used as a model to investigate the response of the hormone.…”
mentioning
confidence: 99%
“…However, another study in Diyala, Iraq, approved that childhood leukemia rate was directly related to age, gender, and blood group, with most recorded cases recorded in the age group 1-5 years. Additionally, it was indicated that blood group O and RhD positive are risk factors for the incidence of ALL in children, and group AB and RhD negative children seemed to be less susceptible [24]. Furthermore, it was found that 36% of the patients had an A+ blood group, followed by O+ (34.6%), and the minority was an AB-(0.5%).…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that estrogen is a mammary gland carcinogen (15) . Therefore, the use of aromatase inhibitors is a common strategy to treat women with hormone receptor-positive breast cancer (16) . Although anastrozole was used as an aromatase inhibitor, this study found a detectable quantity of E2 in the serum of breast cancer patients that was still within normal limits (Table 3), which suggests that there may be other pathways for estrogen synthesis.…”
Section: Discussionmentioning
confidence: 99%